MODEL OF PREPARING A FUTURE TEACHER FOR ETHNOCULTURAL EDUCATION OF JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2010)
The topicality of problem of ethnocultural education is analysed in the article. The structure and conceptual bases of model of training teacher for professional activity in ethnocultural (policultural) educational field are presented.